Ensuring economic security at the regional level as a state influence direction - V.V. Ivaniuta (Економіка, управління та адміністрування)
Understanding of economic security at the legislative level is not defined as an object of state influence in Ukraine; the means of influence, for the most part, are focused on similar ways of managing the regional economic system. The necessity of finding and developing the most effective management methods for ensuring economic security, in particular at the regional level, is shown. It is argued that ensuring regional economic security must be based on the study of the specificity and systematization of regional-specific risks and threats. It is determined that the main purpose of the state administration for ensuring the economic security of the region is to prevent threats and maintain the overall stability of the regional economic system. As a result of the analysis of the main problems of ensuring the economic security of the country, the essence of the economic security of the regions was identified as one of the components of ensuring national security at the present stage of social development. The content of the author's interpretation of the category «economic security of the region» is grounded on the basis of the systematization of risks and threats specific to different types of regions. It is stated that the economic security of a region means a characteristic of the achieved state of its socio-economic system, which is the ability to withstand possible internal and external threats at the expense of available management tools and remedies that cover as much as possible all spheres of society. The distinctive feature of the proposed definition is the identification of risks and threats specific to different types of regions, respectively, and the means of public administration for economic security for each region must be individual.